Irrigation and fertilizer effects on productivity, quality, water use and economics of Yellow Sarson [Brassica rapa (L.) var. trilocularis] - Abhijit Sarma,; JC Das, (Journal of Oilseed Brassica, 2026)
An experiment was conducted to study the effect of irrigation and fertilizer on Yellow Sarson (Brassica rapa L.var. trilocularis (Roxb.) Kitam.) with 4 irrigation regimes viz., irrigation at flowering, irrigation at pod formation,irrigation at flowering and pod formation and conventional practice (rainfed) and 3 levels of fertilizers viz.,60-40-40, 75-50-50 and 90-60-60 N-P2O5-K2O kg/ha during 2012-13 to 2014-15. Two irrigations applied atflowering- and siliqua formation stage recorded higher yield attributes viz., siliqua/plant, siliqua length and numberof seeds/siliqua. Two irrigations at flowering- and pod formation stage also recorded 6.8, 11.6 and 46.9 percenthigher yield over single irrigation at flowering, single irrigation at pod formation and rainfed crop. Among thefertilizer levels, application of 90-60-60 N-P2O5-K2O kg/ha being at par with 75-50-50 N-P2O5-K2O kg/harecorded the highest yield attributes, seed yield, net return and B : C ratio. The highest water use efficiency(WUE) was observed with two irrigations at flowering- and pod formation stage.